1985
DOI: 10.1111/j.2044-8279.1985.tb02617.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between School Motivation, Approaches to Studying, and Attainment, Among British and Hungarian Adolescents

Abstract: SUMMARY.Samples of 614 British and 579 Hungarian pupils aged 13-17 completed an inventory covering 20 sub-scales of school motivation and approaches to studying. Indices of attainment in arts and science were also obtained. The factor structure of the inventory proved to be remarkably stable across nationality and sex, with school motivation accounting for two factors (the emotional and moral domains, and the cognitive domain) and approaches to studying dividing into three (meaning, reproducing, and organking/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
2
5

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 2 publications
0
32
2
5
Order By: Relevance
“…Three approaches to learning are described in the model -surface, deep, and achieving -and each approach has its corresponding motive and strategy (Table 1). Biggs has acknowledged links between his work and that of Entwistle, Hanley, and Hounsell (1979), Entwistle and Kozeki (1985), and Watkins (1983). There are also recognisable links with Heath (1964), Pask (1976), and Schmeck (1983), as well as Saljo (1976a, 1976b) and Fransson (1977).…”
Section: Introductionmentioning
confidence: 94%
“…Three approaches to learning are described in the model -surface, deep, and achieving -and each approach has its corresponding motive and strategy (Table 1). Biggs has acknowledged links between his work and that of Entwistle, Hanley, and Hounsell (1979), Entwistle and Kozeki (1985), and Watkins (1983). There are also recognisable links with Heath (1964), Pask (1976), and Schmeck (1983), as well as Saljo (1976a, 1976b) and Fransson (1977).…”
Section: Introductionmentioning
confidence: 94%
“…Theoretically, enduring patterns of study behaviour may be attributable, for example, to enduring motivational influences, preferred learning styles or habitual ways of engaging learning tasks. However, the most basic understanding of student learning engagement acknowledges sources of variation attributable to the context of learning as well, and this is held, by definition, to be a fundamental phenomenon for which there is also an impressive array of supporting argument (Entwistle and Ramsden 1983). Empirically, the evidence in support of this phenomenon is equally clear and its manifestation (within the concept of study orchestration) has been demonstrated at an individual, as well as a group, level of analysis (Meyer and Muller 1990;Meyer and Dunne 1991).…”
Section: Three Assumptions Related To Study Orchestrationsmentioning
confidence: 99%
“…Les travaux antérieurs ont mis en évidence le caractère prédictif des aptitudes (Zuniga, 1989), des motivations (Biggs, 1984 ;Entwistle et Kozeki, 1985;Entwistle, 1986 ;Ramsden, 1979 ;Viau, 1994 ;Zuniga, 1989), du passé scolaire (Biggs, 1985;Bloom, 1976;Parmentier, 1994), de certains facteurs sociologiques (Dupont et Ossandon, 1994) et de la qualité de la gestion du temps (Adams et Paquet, 1991;Donnay, 1989;Hoff Macan, Shahani, Dipboye et Phillips, 1990;Parmentier, Gathy, Paquet, De Ketele et Denef, 1991) pour la performance académique universitaire. Plus récemment, des chercheurs se sont intéressés aux méthodes et techniques de travail, aspect qualitatif de l'engagement (De Ketele, Draime et Volgaire, 1987;Entwistle, 1978; Entwistle et Ramsden,1983;Entwistle et Waterson, 1988;Marton et Säljö, 1984;Pask, 1976;Romainville, Philippe et Willocq, 1997), et à la métacognition (Biggs, 1985;Flavell, 1976;Noël, 1991;Noël, Romainville et Wolfs, 1995;Romainville, 1992Romainville, , 1993Schunk, 1989;Thiran,…”
unclassified